IRAN AFTER MAHSA AMINI’S DEATH: REVISITING THE DISCOURSE OF RELIGIOUS AUTHORITY IN ISLAM - Ibrahim, Muhammad Faris (Jurnal Penelitian Humaniora, 2024)
This article explores the impact of the death of Mahsa Amini, a woman, at the hands of Iran's moral police, Gasht Ershad, and the subsequent emergence of protests against the country's religious authorities. The central argument delves into the examination of the Religious Authority's role in preserving Islamic values within Iranian society while seemingly encroaching upon the right to freedom of religion, particularly the choice to wear a headscarf. The study reveals that the authoritarianism exhibited by religious authorities in Iran is closely tied to the justification provided by Shi'a theology itself. Furthermore, the influential role of wilāyāt al-Faqīh is instrumental in the gradual establishment of mandatory hijab laws. Ultimately, Mahsa Amini's death is seen as a potential catalyst for re-evaluating the hijab rule amid Iran's political instability, although it does not necessarily undermine the overall authority of religious figures in the country.